Biofabrication of Gold Nanotriangles Using Liposomes as a Dual Functional Reductant and Stabilizer - Soto, Jackeline (2021)
Negatively charged liposomes accomplished both functions as a reducing and stabilizing agent in the synthesis of gold nanotriangles (GNTs). Liposomes are based on a mixture of phospholipids phosphatidylcholine/phosphoglycerol, and they were used as a template phase to perform the GNTs. The method was evaluated under different conditions such as temperature, reaction time, phosphoglycerol chain length, and precursor concentration. Isotropic and anisotropic gold nanoparticles are formed simultaneously during the synthesis. Therefore, by combining centrifugation and depletion flocculation strategies, the sample was concentrated in terms of GNTs from 15% crude to 80% by using sodium dodecyl sulfate (SDS). As a result, a green colored dispersion was obtained containing highly purified, well-defined, negatively charged GNTs, where the edge length of most particles is centered in the range of 60-80 nm with an average thickness of 7.8 ± 0.1 nm. By this purification process, it was possible to highly increase the yield in terms of GNTs. Other surfactants [cetyltrimethylammonium chloride (CTAC), hexadecyltrimethylammonium bromide (CTAB), Tween 20, and dodecyldimethylammonium bromide] were evaluated during the purification stage, and both CTAB and CTAC show similar results to those obtained by using SDS. These GNTs are potential candidates for future applications in molecular imaging, photothermal therapy, drug delivery, biosensing, and photodynamic therapy.